Effect of Positioning on Oxygen Saturation Among Neonates with Respiratory Distress - Kalsoom Shahnawaz Lashari; Lashari, Shaista Gul; Abdul Hameed Radhan; Zamir Ahmed Qambrani; Khuda Bux Khoso; Farzana Shaikh (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the impact of the prone position versus the supine position on oxygen saturation (SpO2) in children with respiratory distress.Study design: Qausi-experimental studyPlace and Duration of Study: Department of Pediatrics, Liaquat University of Medical Health Sciences (LUMHS), Jamshoro, Pakistan, from Apr to Sep 2025.Methodology: The study enrolled a sample size of 100 neonates, who were admitted to the neonatal intensive care unit (ICU) with respiratory distress. Following the initial stabilization, all the neonates were subjected to supplementary oxygen in both supine and prone positions. Demographic and clinical data were gathered. Statistical analysis was done through Statistical Package For Social Sciences (SPSS) version 27.00 with independent sample t-test to compare the mean SpO2 between positions where a p-value